Dampak Coretax System dan Kesadaran Pajak Terhadap Kepatuhan Wajib Pajak UMKM di Pekanbaru dengan Sanksi Pajak sebagai Variabel Moderasi - Viveronika, Agustina; Widayati , Ani (Lembaga Teewan Journal Solutions, 2026)
This study aims to analyze the effect of the Coretax System and tax awareness on MSME taxpayer compliance in Pekanbaru, with tax sanctions as a moderating variable. This research uses a quantitative approach with a survey method. The sample consists of 200 MSME respondents registered at KPP Pratama Pekanbaru Senapelan who have implemented the Coretax System. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS. The results show that the Coretax System has a positive and significant effect on MSME taxpayer compliance. Tax awareness also has a positive and significant effect on taxpayer compliance. Tax sanctions are proven to moderate the relationship between the Coretax System and taxpayer compliance, but do not moderate the relationship between tax awareness and taxpayer compliance. Simultaneously, the Coretax System, tax awareness, and tax sanctions significantly affect MSME taxpayer compliance.